2005
DOI: 10.1364/opex.13.001848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-mixing interference on gain-coupled distributed-feedback lasers

Abstract: The effects of self-mixing interference on gain-coupled (GC) distributed-feedback (DFB) lasers are analyzed. From coupled-wave theory, the oscillation frequency and threshold gain variations are theoretically deduced. The influences on self-mixing from the coupling length coefficient, the linewidth enhancement factor of the GC DFB laser, and the reflection coefficient of the external reflector are discussed along with numerical analysis and are compared with the effects of self-mixing interference of lambda/4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…where h] l is the photon energy and R is the reflectivity of the output facet. We can then obtain the self-mixing power signal by the formula ΔP P l − P l0 (17) where P l and P l0 are the optical power with and without optical feedback, respectively. It should be also noted that we assume the linewidth enhancement factor α 0 for THz QCLs [5].…”
Section: Theoretical Model Of Smi In Thz Complex-coupled Dfb-qclsmentioning
confidence: 99%
See 2 more Smart Citations
“…where h] l is the photon energy and R is the reflectivity of the output facet. We can then obtain the self-mixing power signal by the formula ΔP P l − P l0 (17) where P l and P l0 are the optical power with and without optical feedback, respectively. It should be also noted that we assume the linewidth enhancement factor α 0 for THz QCLs [5].…”
Section: Theoretical Model Of Smi In Thz Complex-coupled Dfb-qclsmentioning
confidence: 99%
“…From this point of view, some early studies investigated the properties of SMI in index-coupled diode lasers using the coupled wave theory, and the results show that the cosine-like self-mixing signal is similar to that from a single-mode FP laser [15,16]. Furthermore, some studies also have shown that SMI sensors based on gain-coupled DFB lasers exhibit high accuracy [17]. However, a DFB laser with a grating etched into its upper cladding layer has an increased waveguide loss through the top contact layer, and this may in turn decrease its performance [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the isolation stage of the system, very low power light is sufficient to cause self-mixing within DFB lasers. 5 The self-mixing of the laser made the vibrometer system sensitive to displacement of the target rather than velocity. Therefore there was a greater error in the demodulated velocity signal at low velocities compared with the demodulated velocity signal obtained from higher velocities of the target.…”
Section: Figure 2: Lens-target Assembly With Excited Target Facementioning
confidence: 99%